Learning to Read and Write the Qur'an and Memorize Short Letters for Children in Jangga Village, Losarang District, Indramayu Regency - Muhamad Aditiyah (Konsultan Jurnal Ilmiah Indonesia, 2024)
The purpose of implementing the community service program (PkM) is to improve understanding, train memory, beliefs and apply religious values ​​in everyday life for children in Jangga Village. This program uses several methods such as lecture methods, questions and answers, Iqro methods. Or Juz Amma, By holding this program, students hope that children in Jangga Village can understand and practice religious life in Jangga Village better. The result of this Community Service is that religion has an important role in life. There are many functions of religion that we can feel when living our daily lives. The existence of religion aims to create order (rules), this comes from God, where it is able to guide humans to become someone who is rational and tries to find happiness, both in the world and in the hereafter.